Reduction of Interleukin-6 after PRP-Exosomes Treatment in A Mouse Model of Androgenetic Alopecia - Ellistasari, Endra Yustin; Widhiati, Suci; Julianto, Indah; Rosmarwati, Ervina; Monica, Pristia Widya; Yasmin, Aulia (Universitas Muhammadiyah Surakarta, 2024)
Purpose: This study aim to determine the role of platelet-rich plasma (PRP) exosomes as anti-inflammatory (IL-6) in a mouse model of androgenetic alopecia. Methodology: There are four group of androgenetic alopecia mice model with no treatment group (control group, K1), group treated with PRP-exosomes (K2), group treated with 5% topical minoxidil (K3) and the last group treated with combination of PRP-exosomes and 5% topical minoxidil (K4). All of the group was evaluated clinically and immunohistochemical examination of IL-6 was performed on the 32nd day. Results: Better hair growth results were obtained in the treatment group compared to the control group. In clinical evaluation, K4 had the best results, followed by K2 and K3. The expression of IL-6 is highest in the K1, followed by K4, K2 and K3 and statistically significant. Applications/Originality/Value: PRP-exosomes can enhance hair growth in androgenetic alopecia mice model. IL-6 expression in the control group is significantly higher than in the treatment group.